2020
DOI: 10.1186/s12883-020-01780-7
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid metabolism, lipid metabolism, and oxidative stress are associated with post-stroke depression: a metabonomics study

Abstract: Background Post-stroke depression (PSD) is a mood disorder characterized by depression and anhedonia caused by stroke. Metabolomics identified metabolites associated with PSD, but previous studies are based on gas chromatography (GC)/mass spectrometry (MS). This study aimed to perform a liquid chromatography (LC)-MS-based metabolomics study of the plasma metabolite profiles between patients with PSD and controls. Methods This was a prospective study of patients with stroke enrolled between July and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…As one of the cerebral diseases in the "brain program, " stroke is listed as the primary cause of disability and death (Wang et al, 2013(Wang et al, , 2017 due to its characteristics of high incidence, high disability rate, and high mortality rate. The existing basic researches mainly concentrate on proteomics, genomics, and metabolomics (Nguyen et al, 2016;Hasin et al, 2017;Wang et al, 2020). Neuroimaging technology is a research focus in the field of in vivo research on post-stroke injury.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the cerebral diseases in the "brain program, " stroke is listed as the primary cause of disability and death (Wang et al, 2013(Wang et al, , 2017 due to its characteristics of high incidence, high disability rate, and high mortality rate. The existing basic researches mainly concentrate on proteomics, genomics, and metabolomics (Nguyen et al, 2016;Hasin et al, 2017;Wang et al, 2020). Neuroimaging technology is a research focus in the field of in vivo research on post-stroke injury.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous works, we found that the amount of glycerin was remarkably increased in depression mice. In contrast, ACE effectively reduced the glycerin level (61,62). Spermidine could promote autophagic activation, which may induce neuronal damage in the hippocampus (61,62).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, ACE effectively reduced the glycerin level (61,62). Spermidine could promote autophagic activation, which may induce neuronal damage in the hippocampus (61,62). ACE administration effectively suppressed the level of spermidine FIGURE 5 | Differential metabolites expression in the brain of mice between the CON, CORT, and ACE groups.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with PSD have higher mortality rates [ 7 , 10 ], more pronounced cognitive deficits, more long-term disability, lower quality of life and higher rates of suicidal ideation as compared to post-stroke patients without depression, indicating that early detection and treating depression are important after a stroke [ 11 , 12 , 13 , 14 ]. Thus, the consequences of not detecting depression symptoms at an early stage can be relevant for the patient as well as health systems [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%